Evaluasi Implementasi Penilaian Hasil Belajar Berdasarkan Kurikulum 2013 oleh Guru Bahasa Inggris dan Bahasa Indonesia di MTS Ja-Alhaq Kota Bengkulu - Heny Friantary; Feny Martina (LP4MK STKIP PGRI Lubuklinggau, 2018)
The objective of this research was to describe the results of the evaluation of the 2013 curriculum implementation process in the assessment of learning outcomes conducted by Indonesian and English language subject teachers in in the Bengkulu City Ja-Alhaq MTS and explain the gap between absolute standards of implementation and the implementation of learning outcomes assessment conducted by Indonesian subject teachers and English in MTS Ja-Alhaq Kota Bengkulu. The research method used is descriptive qualitative method. Data collection techniques by observation, interviews, and documentation. The data analysis technique starts from identifying data, classifying data, presenting data and drawing conclusions. The results of the study showed that the process of implementing student learning outcomes conducted by English teachers of Indonesian language teachers was not fully in accordance with what was requested by K13, the assessment of aspects of knowledge competence was still dominated by written test techniques, and assessment for skills competency measurement was only done with assessment techniques practice. Then, there are some gaps between the absolute standards of implementation and the implementation of student learning outcomes assessment conducted by English teachers and Indonesian teachers who are the subjects of this research.